Sexual and reproductive health knowledge, attitudes, and behaviors: A survey of 12-17 year old Sudanese refugees in Chad. - Theodora Varelis; Vincent de Paul Allambademel; Alexis Ngarmbatedjimal; Alladoum Ndingayande; Aminata Diarra; Katchebe Vourbane; Robert Madjigoto; Samy Luketa; Sara E Casey (Public Library of Science (PLoS), 2024)
Adolescents living in humanitarian settings are often at a higher risk of negative sexual and reproductive health outcomes, and yet, limited information is available on adolescents' experiences and needs in these settings while available services do not always correspond to their needs. This study explored knowledge, attitudes, and behaviors relating to sexual and reproductive health among 12-17 year old refugees from Darfur currently living in two refugee camps in eastern Chad. The research team conducted a cross-sectional survey of 689 adolescent girls and boys, informed by participatory research activities, to explore key sexual and reproductive health topics. This study found that sexual and reproductive health knowledge among adolescents is low, with only 69.1% able to identify at least one modern contraceptive method. Early marriage was uncommon (5% of girls, 0.8% of boys), but 17.6% of adolescents had already had a romantic relationship. Few adolescents (11.4%) had ever had sex, but among these adolescents,18.4% reported using a condom the last time they had sex. No boys reported current modern contraceptive use, but 28.3% of girls, both married and unmarried, reported current use. These findings demonstrate the importance of making sexual and reproductive health services in humanitarian settings more adolescent-responsive and minimizing barriers to access, including addressing community stigma surrounding adolescents' use of sexual and reproductive health services and increasing trust in the confidentiality of sexual and reproductive health services in the camps.